Anti-TNF Therapeutic Drug Monitoring in Postoperative Crohn's Disease. (27th January 2018) - Wright, Emily K; Kamm, Michael A; De Cruz, Peter; Hamilton, Amy L; Selvaraj, Fabiyola; Princen, Fred; Gorelik, Alexandra; Liew, Danny; Prideaux, Lani; Lawrance, Ian C; Andrews, Jane M; Bampton, Peter A; et al.
Abstract: Background: Anti-TNF prevents postoperative Crohn's disease recurrence in most patients but not all. This study aimed to define the relationship between adalimumab pharmacokinetics, maintenance of remission and recurrence. Methods: As part of a study of postoperative Crohn's disease management, some patients undergoing resection received prophylactic postoperative adalimumab. In these patients, serum and fecal adalimumab concentration and serum anti-adalimumab antibodies [AAAs] were measured at 6, 12 and 18 months postoperatively. Levels of Crohn's disease activity index [CDAI], C-reactive protein [CRP] and fecal calprotectin [FC] were assessed at 6 and 18 months postoperatively. Body mass index and smoking status were recorded. A colonoscopy was performed at 6 and/or 18 months. Results: Fifty-two patients [32 on monotherapy and 20 on combination therapy with thiopurine] were studied. Adalimumab concentration did not differ significantly between patients in endoscopic remission vs recurrence [Rutgeerts ≥ i2] [9.98µg/mL vs 8.43 µg/mL, p = 0.387]. Patients on adalimumab monotherapy had a significantly lower adalimumab concentration [7.89 µg/mL] than patients on combination therapy [11.725 µg/mL] [ p = 0.001], and were significantly more likely to have measurable AAA [31% vs 17%, p = 0.001]. Adalimumab concentrations were lower in patients with detectable AAA compared with those without [3.59 µg/mL vs 12.0 µg/mL, p < 0.001]. Adalimumab was not detected in fecal samples. Adalimumab serum concentrations were lower in obese patients compared with in non-obese patients [ p = 0.046]. Conclusion: Adalimumab concentration in patients treated with adalimumab to prevent symptomatic endoscopic recurrence postoperatively is, for most patients, well within the therapeutic window, and is not significantly lower in patients who develop recurrence compared with in those who remain in remission. Mechanisms of anti-TNF failure to prevent postoperative recurrence remain to be determined in these patients.